Uncommon traveler : Mary Kingsley in Africa - Brown, Don, 1949- (Boston : Houghton Mifflin Co., 2000)
A brief biography of the self-educated nineteenth-century Englishwoman who traveled alone through unexplored West Africa in 1893 and 1894.(Gr.1-4)
Includes bibliographical references (p. [34]).
AD 550
Accelerated Reader AR
Keywords: Kingsley, Mary Henrietta, -- 1862-1900 -- Juvenile literature; Explorers -- Africa, West -- Biography -- Juvenile literature; Explorers -- Great Britain -- Biography -- Juvenile literature; Women explorers -- Africa, West -- Biography -- Juvenile literature; Women explorers -- Great Britain -- Biography -- Juvenile literature; Women -- Biography -- Juvenile literature; Africa, West -- Discovery and exploration -- British -- Juvenile literature; Africa, West -- Discovery and exploration -- Juvenile literature